2016
DOI: 10.1111/ggi.12745
|View full text |Cite
|
Sign up to set email alerts
|

Health and happiness among community‐dwelling older adults in Domkhar valley, Ladakh, India

Abstract: Subjective quality of life among older adults in Domkhar was higher than Japanese controls despite a higher rate of difficulty in basic activities of daily living. We have to consider prevention, treatment, and care of not only diseases and disabilities, but also loneliness for the older adults. Geriatr Gerontol Int 2017; 17: 480-486.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…According to Van Leeuwen et al [14], financial resources affect older adults' quality of life, feelings of independence, and access to a comfortable life. Additionally, the present findings were consistent with those of previous studies [7,14,21,22,23] that reported that depression and health status were closely related to happiness. Further, Kim, Song, Kim, and Park [22] reported that depressive symptoms were powerful predictors of happiness in older women living alone.…”
Section: Associations Between Subject Characteristics Depression Ansupporting
confidence: 93%
“…According to Van Leeuwen et al [14], financial resources affect older adults' quality of life, feelings of independence, and access to a comfortable life. Additionally, the present findings were consistent with those of previous studies [7,14,21,22,23] that reported that depression and health status were closely related to happiness. Further, Kim, Song, Kim, and Park [22] reported that depressive symptoms were powerful predictors of happiness in older women living alone.…”
Section: Associations Between Subject Characteristics Depression Ansupporting
confidence: 93%
“…The study results showed that older women living in South Korea had a moderate degree of happiness (3 on a scale of 5). The median level of happiness among the participants was lower than that in other Asian countries, such as Japan (61.0 on a scale of 100), Thailand (74% of participants reported moderate or high happiness), Hong Kong (7.4 on a scale of 10) and India (74.3 on a scale of 100) . However, the level of happiness in the present study cannot be directly compared with that in other countries, because these prior studies included all community‐dwelling older adults, not just women who were living alone.…”
Section: Discussionmentioning
confidence: 60%
“…The effect of economic status on happiness was also different from prior studies, because we focused on perceived economic satisfaction. A study comparing the levels of happiness in Japan and India showed that economic status was not associated with the level of happiness …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations